The dark side of democracy : explaining ethnic cleansing - Mann, Michael, 1942- (Cambridge University Press, 2004)
This comprehensive study of international ethnic cleansing provides in-depth coverage of its occurrences in Armenia, Nazi Germany, Cambodia, Yugoslavia, and Rwanda, as well as cases of lesser violence in early modern Europe and in contemporary India and Indonesia. After presenting a general theory of why serious conflict emerges and how it escalates into mass murder, Michael Mann offers suggestions on how to avoid such escalation in the future. Michael Mann is the author of Fascists (Cambridge, 2004) and The Sources of Social Power (Cambridge 1986). The Dark Side of Democracy is the most comprehensive study of ethnic cleansing.